Assessment of cardiometabolic risk in children in population studies: underpinning developmental origins of health and disease mother–offspring cohort studies. (10th April 2015) - Huang, R.-C.; Prescott, Susan L.; Godfrey, Keith M.; Davis, Elizabeth A.
Abstract Pregnancy and birth cohorts have been utilised extensively to investigate the developmental origins of health and disease, particularly in relation to understanding the aetiology of obesity and related cardiometabolic disorders. Birth and pregnancy cohorts have been utilised extensively to investigate this area of research. The aim of the present review was twofold: first to outline the necessity of measuring cardiometabolic risk in children; and second to outline how it can be assessed. The major outcomes thought to have an important developmental component are CVD, insulin resistance and related metabolic outcomes. Conditions such as the metabolic syndrome, type 2 diabetes and CHD all tend to have peak prevalence in middle-aged and older individuals but assessments of cardiometabolic risk in childhood and adolescence are important to define early causal factors and characterise preventive measures. Typically, researchers investigating prospective cohort studies have relied on the thesis that cardiovascular risk factors, such as dyslipidaemia, hypertension and obesity, track from childhood into adult life. The present review summarises some of the evidence that these factors, when measured in childhood, may be of value in assessing the risk of adult cardiometabolic disease, and as such proceeds to describe some of the methods for assessing cardiometabolic risk in children.